Social Media Content As Predictor Of Mindset And Communication Among Central Java Gen Z Workers - Kristiana Dewi, Danar; Arisanty, Melisa; Riady, Yasir; Ajmal, Muhammad; Bintarti, Arifah (KOMUNIKA, 2026)
This study analyzes the relationship between social media consumption shapes the mindset and communication patterns of Generation Z in professional settings. Drawing on a survey of 432 participants and applying Pearson correlation, Kruskal-Wallis, and multiple linear regression analyses, the research found that the duration of social media use is not statistically significantly related to Generation Z's mindset, though it shows a marginal association with communication model scores. By contrast, the nature of the content consumed has a notable influence: motivational, business, and educational content are associated with a growth mindset, whereas passive entertainment content tends to reinforce a fixed mindset. Regression results further indicate that content type and content relatability are the strongest predictors of both mindset and communication orientation, jointly explaining approximately 30% of the variance observed. These results underscore the critical role of digital literacy in content selection over mere screen time. Additionally, the study reveals gender-based variations in content preferences, with male users favoring self-improvement content and female users showing broader engagement with entertainment and lifestyle content, with implications for cross-generational communication strategies. The findings offer practical recommendations for educational institutions, corporate entities, and digital platforms to enhance content literacy and foster more effective intergenerational communication in the workplace.